Implementation of the theory of gradual formation of mental actions in the format of a distance lecture - Анжелика Н. Пронина; Татьяна П. Будякова (Rossijskij psihologičeskij žurnal., 2023)
Introduction. The article deals with methodological and conceptual issues of the implementation of the theory of gradual formation of mental actions by P. Ya. Galperin in the conditions of distance learning in higher education. We have analyzed for the first time the potential of P. Ya. Galperin’s theory of the gradual formation of mental actions for methodological support of distance university lectures and described the vectors of its transformation in connection with the electronic learning format. Methods. The study material was lectures conducted on the YouTube platform. The study participants were students and teachers from Bunin Yelets State University who gave them batch lectures using the YouTube service. The method of active interviews with students and teachers was applied as a research tool. The results were processed using a meaningful content analysis. Results. It was found that both the advantages and disadvantages of distance lectures reflect the psychology of assimilation of mental actions described in P. Ya. Galperin theory. Thus, to meet the quality standards of education, the content of the educational materials presented in the lecture must meet the requirements of the third type of learning, according to P. Ya. Galperin. The generality and completeness of the educational material should be ensured, subject to the condition that the volume of the educational material does not exceed the traditional lecture’s volume. Discussion. The results obtained indicate that the distance learning form does not exclude the successful application of the fundamental provisions of the theory of the gradual formation of mental actions, which once again proves the importance of this theory for building successful learning technologies regardless of the learning format. In the context of the development of this theory, the opinion is expressed about the need to teach students the technique of processing the written form of a distance lecture, translating it into a mini-abstract format.